The Google Classroom – Assisted English Writing Classroom Practices: An Indonesian EFL Teacher's Experiences - Sri Partini; Maman Suryaman; Mobit Mobit (INTERACTION: Jurnal Pendidikan Bahasa, 2022)
This research aims to investigate a teacher’s experiences and difficulties of Google Classroom-assisted teaching writing. This research used narrative inquiry as a research design. It used interview as the data collection technique to answer the research questions. One English teacher who taught in two grades of Vocational School in Karawang, Indonesia participated in this research. The finding shows that the teacher had particular ways to deliver the material assisted by Google classroom. To work with the Google Classroom, the teacher also used the PJBB Pembelajaran Jarak Jauh to deliver the material which was fit to school curriculum. To assess the students, the teacher used to ask the students to write down the answers of its task, and then they take the picture of its answers so they send it into Google Classroom. To conclude, this study shows that the internet data, device, student and teachers' ability, and so many other factors were given a big impact on online class, especially on Google Classroom-assisted teaching writing. The next researcher hopefully will conduct the research in the different focus of study, different learning media, and different classes or grades and also the next researcher hopefully conduct it with more participants. Because of this study just focused on writing narrative text lessons assisted by Google Classroom, the future research with another focus of study for example reading, speaking, listening, and so on hopefully will be conducted.